PERTIMBANGAN HAKIM DALAM PENJATUHAN PIDANA DENDA PADA TINDAK PIDANA ILLEGAL FISHING - Laia, Yudisa (Jurnal Panah Hukum, 2025)
Any type of fishing activity that breaches the Law on Fisheries' requirements as well as other rules and regulations still in effect in this republic is considered illegal fishing. Decision Number: 34/Pid.Sus-Prk/2017/PN.Ran was one of the unlawful fishing offenses that a panel of judges at the Ranai District Court tried. In this ruling, the judge determined that the defendant had been shown legally and credibly guilty of engaging in illicit fishing. The study, which is part of Decision Study Number 34/PID.SUS-PRK/2017/PN.RAN, is titled The Judge's Consideration of the Criminal Act of Illegal Fishing Committed by Foreign Citizens. Normative legal research employing the statutory approach, case approach, and analytical method is the sort of study that is done. Primary, secondary, and tertiary data were used in the data gathering process. Deductive reasoning is employed to arrive at conclusions from the descriptive qualitative data analysis. The offender was sentenced to a fine of Rp. 500,000,000 (five hundred million rupiah) by the court, who based his decision on study findings and discussion. If the fine is not paid, a reduced punishment of 4 (four) months would be imposed instead. Researchers' analysis, however, indicates that this sentence is insufficient to deter the offender; instead, the judge should impose a fine and imprisonment commensurate with the charges against the offender in order to deter future crimes and discourage those in other nations from committing the same offense. carry out the same action.